Digital Detox and Mindfulness: Psychological Effects of Reducing Mobile App Usage Among University Students - Norquziyeva, Zebo; Davlatova, Zebo; Kholnazarov, Umid; Edilboyev, Unarbek; Sattorova, Zilola; Xamrakulova, Kamola; Nurullayeva, Nodira; Shabbazova, Dilfuza (Malikussaleh University, Aceh, Indonesia, 2025)
In the contemporary digital era, college students are among the most frequent users of mobile applications and social media systems, raising substantial worries around addiction to technology. Although online resources provide many benefits, their improper usage and excessive reliance present significant risks. This research examines the impacts of a one-day Digital Detox (DD) program on undergraduates in Uzbekistan, concentrating on the consequences of refraining from smartphone use. The detox camp, modeled after similar programs, sought to assess the effects of a total DD. The research used qualitative approaches, conducting comprehensive conversations with respondents to evaluate improvements in self-awareness, connections with others, and general well-being. The results showed that people were more aware of themselves, had better connections, and felt much more relaxed. There were problems like Nomophobia (the fear of being without a mobile device) and FOMO (the fear of missing out).The findings demonstrate that DD programs significantly reduce digital reliance and promote conscious technology use among students. This study improves what we already know about the benefits of DD approaches and points out areas that need further research and application.